LOCAL POLITICAL DYNAMICS IN THE GENERAL ELECTION DIRECTLY CONDUCTED TO VOTE FOR DISTRICT HEADS (PILKADA) IN BADUNG REGENCY IN 2005 - Oka Wisnumurti, Anak Agung Gede; Ardika, I Wayan; Parimartha, I Gde; Pasek Diantha, I Made (E-Journal of Cultural Studies; Vol. 5, No. 2 Juli 2011)
The general election directly conducted to vote for the regent and vice regent(Pemilihan Kepala Daerah, abbreviated to Pilkada) by the people in Badung Regency in2005 was the first one. The people’s direct involvement in the local political life movedhighly dynamically. The struggle for power by various strengths affected variousdimensions of the people’s lives; therefore, it is interesting to investigate the localpolitical dynamics in the Pilkada directly conducted in Badung Regency in 2005 in theperspective of cultural studies. There are three problems formulated in this study. Theyare (1) what was the dynamics of the Pilkada directly conducted in Badung Regency in2005 like?; (2) how the relation of strengths affected the local political dynamics in thePilkada directly conducted in Badung Regency in 2005?; (3) what were the implicationsand meanings of the local political dynamics of the Pilkada directly conducted in BadungRegency in 2005?The results of the study show that fluctuative changes took place continuouslywith regard to the form and functions of societal structure. Culturally, the people’sideology changed from being mono centric into being multi centric. The relation ofstrengths became segmented into three main strengths forming a new formation ofstrength referred to as trisula. This led to an institutional configuration, differentiation ofpower and locality sedimentation, and provided meanings to competition and tolerance,emancipatory, political comodification, adaptive leadership and local democratic culturalstrengthening.
Keywords: dynamics, local politics, and direct pilkada in Badung Regency